Biocompatibility and osteoinductive ability of casein phosphopeptide modified polyetheretherketone - Qiu, Peng; Wang, Pin; Liu, Min; Dai, Tao; Zheng, Min; Feng, Le (Frontiers in Bioengineering and Biotechnology, 2023)
Polyetheretherketone (PEEK) is a potential implant material for dental application due to its excellent mechanical properties. However, its biological inertness and poor osteoinductive ability limited its clinical application. Based on a lay-by-layer self-assembly technique, here we incorporated casein phosphopeptide (CPP) onto PEEK surface by a simple two-step strategy to address the poor osteoinductive ability of PEEK implants. In this study, the PEEK specimens were positively charged by 3-ammoniumpropyltriethoxysilane (APTES) modification, then the CPP was adsorbed onto the positively charged PEEK surface electrostatically to obtain CPP-modified PEEK (PEEK-CPP) specimens. The surface characterization, layer degradation, biocompatibility and osteoinductive ability of the PEEK-CPP specimens were studied in vitro. After CPP modification, the PEEK-CPP specimens had a porous and hydrophilic surface and presented enhanced cell adhesion, proliferation, and osteogenic differentiation of MC3T3-E1 cells. These findings indicated that CPP modification could significantly improve the biocompatibility and osteoinductive ability of PEEK-CPP implants in vitro. In a word, CPP modification is a promising strategy for the PEEK implants to achieve osseointegration.